Diseño de una interfaz usando Python para la identificación de asimetrías temporales en la marcha de personas con prótesis de miembro inferior (2023)
Lower limb amputations cause irreversible changes and modify the gait cycle, leading to a decrease in the autonomous locomotion capacity of affected individuals. Gait is a synchronous movement of the lower limbs, and any alteration in its determinants results in the concept of asymmetry.